STUMBLING TOWARDS THE CONSTITUTION. (14th March 2016) - Adams, Thomas
Abstract : ONE way in which governments may exercise political control over their subjects is by removing their status as citizens. Doing so – denying the individual the political and social rights that are constitutive of full membership of their community – involves making a radical choice, and accordingly such a decision must be properly regulated. One of the ways in which UK law does so is by preventing the exercise of the broad statutory power to rescind the citizenship of a UK national because it is "conducive to the public good", where doing so would render that person stateless (British Nationality Act 1981, s. 40(2), (4)). Individuals may only be stripped of their citizenship under this provision on the condition that they remain full members of another political community.